2014
DOI: 10.4172/2157-7099.1000272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kurdistan Honey on the Tongue of Chemotherapy Treated Albino Rats (Immunohistochemical Study)

Abstract: Background and Objectives: Mucositis can be a dose-limiting toxicity of cancer chemotherapy with direct effects on patient survival; therefore an effective intervention is considered a high priority in cancer patient. The aim of the present study was to evaluate the effectiveness of honey as a preventive treatment for the methotrexate (MTX) induced oral mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…The findings of the present study were in line with other studies that reported similar changes in tongue mucosa of experimental rats induced by other cytotoxic drugs such as 5‐Fluorouracil and methotrexate . In addition, a more recent study showed that irinotecan administration in rats led to an intestinal mucosal damage that was manifested by disorganized epithelial architecture, epithelial damage, atrophy of the villi and inflammatory cellular infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study were in line with other studies that reported similar changes in tongue mucosa of experimental rats induced by other cytotoxic drugs such as 5‐Fluorouracil and methotrexate . In addition, a more recent study showed that irinotecan administration in rats led to an intestinal mucosal damage that was manifested by disorganized epithelial architecture, epithelial damage, atrophy of the villi and inflammatory cellular infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…The affected cells revealed vacuolated cytoplasm with condensed pyknotic nuclei. Our results were in harmony with Al Refai [ 30 ]. These degenerative changes could be due to the inhibition of topoisomerase I, which results in DNA damage and fragmentation.…”
Section: Discussionsupporting
confidence: 93%